Pengaruh Pelatihan dan Disiplin Kerja terhadap Kinerja Karyawan di CV Nina Etik Garment Indonesia - Nur Puji Astutik; Imam Baidlowi; Toto Heru Dwihandoko (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study aims to analyze the influence of training and work discipline on employee performance in CV. Nina Etik Garment Indonesia. The approach used is a quantitative method by distributing questionnaires to 40 respondents who are permanent employees of the company. The independent variables in this study are training and work discipline, while the dependent variables are employee performance. The results of the study show that training has a positive effect on performance, but this influence is not optimal because there are still obstacles in the form of lack of understanding of the material by some employees. This shows that the effectiveness of training needs to be improved, both in terms of delivery methods, the quality of instructors, and the suitability of materials with work needs. Meanwhile, work discipline has been proven to have a significant influence on improving employee performance. Discipline factors, such as punctuality, compliance with rules, and responsibility for completing tasks, are important aspects that drive productivity. This research also found that undisciplined behavior still often occurs, such as being late or not complying with work procedures, which ultimately has an impact on decreasing the effectiveness of the company's operations. Simultaneously, training and work discipline have a significant effect on employee performance, so these two factors need to receive serious attention from management. The practical implication of this research is the need for companies to improve the quality of training programs, both technical and non-technical, so that employees are able to master skills relevant to their work. In addition, the implementation of a more firm, consistent, and measurable work discipline supervision system is also an important strategy to form a professional work culture.